Metallic Line Doubling in the Spectra of the Variable Star R Scuti. Issue Volume 14:Issue S343(2019) (August 2018) - Chafouai, K.; Benhida, A.; Sefyani, F.; Ghout, A.; Benkhaldoun, Z.; Mathias, P.; Gillet, D.; El Jariri, Y.
Abstract: In this work, we present spectroscopic results of the variable star R Scuti, obtained during the campaign of measures led in 2016 at the Oukaimeden observatory in Morrocco. High resolution spectra (R ≍ 12 000) were obtained between 4289 Å and 7125 Å. This intensive observing campaign spanned over 26 nights from June to November 2016.